Physiography potentiality of Spanish fir forests (Abies pinsapo Boiss.) in Andalucía - Navarro Cerrillo, R. Mª.; Lara Fernández, A.; Blanco Oyonarte, P.; Calzado Martínez, C.; López Quintanilla, J.; Fernández Cancio, A.; Guzmán Álvarez, J. R.; Sánchez Salguero, R. (Forest Systems, 2006)
Spanish fir (Pinsapo) forests (Abies pinsapo Boiss.) are one of the most outstanding formations in the south of Spain. To find out their potentiality, a regression model (MARS®) based on logistic regression has been used. Physiography variables used as predictors were: altitude, insolation, and the Compound Topographic Index. The dependent variable used was the present distribution of the species, for which the largest number possible of locations in their principal nuclei were reviewed, i.e. Sierra de las Nieves (Málaga), and Serranía de Ronda and Grazalema (Málaga-Cádiz). The potentiality model has shown an optimal area of 1,332 ha and a mean potentiality area of 18,048 ha. The distribution pattern obtained was fairly irregular and was adapted to the complex physiography of the mountains in south-eastern Spain. The main inconsistency of the model presented with previous potential vegetation models lay in the absence of Spanish fir forests in the most basal and warmest parts of Yunquera and the Sierra de Grazalema.